RL for Latent MDPs: Regret Guarantees and a Lower Bound - Kwon, Jeongyeol; Efroni, Yonathan; Caramanis, Constantine; Mannor, Shie (NeurIPS 2021, 2021)
In this work, we consider the regret minimization problem for reinforcement learning in latent Markov Decision Processes (LMDP). In an LMDP, an MDP is randomly drawn from a set of M possible MDPs at the beginning of the interaction, but the identity of the chosen MDP is not revealed to the agent. We first show that a general instance of LMDPs requires at least Ω((SA)M) episodes to even approximate the optimal policy. Then, we consider sufficient assumptions under which learning good policies requires polynomial number of episodes. We show that the key link is a notion of separation between the MDP system dynamics. With sufficient separation, we provide an efficient algorithm with local guarantee, [i.e.,] providing a sublinear regret guarantee when we are given a good initialization. Finally, if we are given standard statistical sufficiency assumptions common in the Predictive State Representation (PSR) literature (e.g., [boots2011online]) and a reachability assumption, we show that the need for initialization can be removed.